Effect of BN content on the mechanical and dielectric properties of porous BNp/Si3N4 ceramics. Issue 1 (January 2016) - Feng, Yurun; Gong, Hongyu; Zhang, Yujun; Wang, Xianli; Che, Songwei; Zhao, Yujun; Guo, Xue
Abstract: Porous BNp /Si3 N4 ceramics were prepared by gas pressure sintering method as a candidate wave-transparent material. The effects of BN particle additions ranging from 0 wt% to 15 wt% on the phase compositions, microstructures, mechanical performance and dielectric properties were investigated. With the increase of BN content, the apparent porosity of the BN/Si3 N4 ceramics increased greatly from 2.3% to 21.2%. Although the mechanical properties were partially weaken, the dielectric performance of the porous BN/Si3 N4 was largely enhanced at the same time. For the 10% BN/Si3 N4 porous composite ceramics, the permittivity and dielectric loss was 33.5% and 62.2% lower than that of the porous Si3 N4 without BN content, respectively. Specifically, when 10% BN particles were added, the porous BNp /Si3 N4 has a porosity of 20.5% and the permittivity and dielectric loss were 5.14 and 0.0085 respectively with bending strength of 190.1 MPa and fracture toughness of 4.16 MPa m 1/2, which can meet the required value of wave transparent materials.